EFEKTIFITAS PELAYANAN ADMINISTRASI PERTANAHAN DI KOTA PEKANBARU - Teguh Mulyono; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The National Land Agency conducts land certification services, one of which is the transfer of land rights. Currently, many communities have not registered their land, lack of socialization of land registration procedures, objectives of land registration, lack of knowledge of land law grounds, and ineffective service delivery. This study aims to determine the effectiveness of Land Administration Services and to determine the factors that affect the service of Land Administration at the BPN Office Kecamatan Tampan. Based on the effectiveness theory of S. Siagian namely, Clarity of goals to be achieved, Clarity of goal achievement strategy, Process analysis and formulation of a solid policy, Mature Planning, Preparation of appropriate programs, the availability of facilities and work infrastructure. The factors that affect the Limited Quality of Resources and Lack of information. Research location at BPN office Pekanbaru city. The research informants are the head of BPN, BPN staff, Head of Land Rights and Land Registry, Koflik and Case Dispute Disputes as well as the community taking care of the land certificate. This research uses qualitative research method with descriptive analysis by using data collection method technique by interview, observation and documentation. The results showed that the effectiveness in the Administration of Land Administration at BPN Kecamatan Tampan office showed that there was a problem at the time of handling which was not in accordance with the existing regulations. The cost of taking care of the certificate is appropriate. BPN employees are given the opportunity to attend technical and non technical education and training. Coordination of kelurahan and BPN in the land administration process is needed, so there is no waiting list that is so long. Public service one of the fulfillment of welfare then automatically becomes the fulfillment of community rights. Keywords: Effectiveness, Public Service, Land Administration and National Land Agency